2019
DOI: 10.1108/bjm-01-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of business model innovations on SME’s innovativeness and performance

Abstract: Purpose Business model innovations (BMIs), their drivers and outcomes are attracting increasing attention in academic literature. However, previous studies have mainly focused on large companies, while knowledge of BMI in small-to-medium-sized enterprises (SMEs) is limited. Therefore, the purpose of this paper is to add new insights into how related BMI drivers, practices and outcomes are in relation to SMEs. Design/methodology/approach An extensive review of the existing literature was performed. Consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…SEM are multivariate models used to model causal structures in data. For example, they have been used by (Gatautis et al , 2019; Wang, 2019) to analyse the effect of innovation on firm performance. The interest of SEM lies essentially in its ability to simultaneously test the existence of causal relationships between several variables, including moderators and mediators while incorporating measurement errors (Bagozzi, 1980).…”
Section: Methods and Data Measuresmentioning
confidence: 99%
“…SEM are multivariate models used to model causal structures in data. For example, they have been used by (Gatautis et al , 2019; Wang, 2019) to analyse the effect of innovation on firm performance. The interest of SEM lies essentially in its ability to simultaneously test the existence of causal relationships between several variables, including moderators and mediators while incorporating measurement errors (Bagozzi, 1980).…”
Section: Methods and Data Measuresmentioning
confidence: 99%
“…The results showed that business strategies focused on the internal environment, which the company can directly control, increase confidence in planning future innovations. An important part of the innovation activities of small and medium-sized enterprises is the implementation of business model innovation practices, which has a positive impact on necessary strategic and architectural changes in the business model, which will positively affect company's innovation and overall performance (Gatautis et al 2019). The innovation potential and competitiveness of small and medium-sized enterprises increases with the increasing level of the controlling management of the company, especially with a focus on the future results of the company (Pisar and Bilkova 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, on reading the full text, we concluded that they did not address firm innovation or gender adequately to justify inclusion. For example, Gatautis et al (2019) present an interesting study on how business model innovation influences the innovativeness of an SME. They mention gender as one of the properties of an SME in the abstract.…”
Section: Systematic Reviewmentioning
confidence: 99%